THE EFFECT OF MICROTEACHING AND GUIDED FIELD PRACTICE (PLT) ON READINESS TO BECOME PROFESSIONAL TEACHER OF THE ACCOUNTING EDUCATION STUDENT STATE UNIVERSITY OF YOGYAKARTA CLASS OF 2015 - Nabila Sofiarani; Arief Zuliyanto Susilo (Jurnal Pendidikan Akuntansi Indonesia, 2019)
This research aims to determine whether there is an effect of the Microteaching Quality and Guided Field Practice (PLT) on Readiness to Become Professional Teacher. This research uses a quantitative approach with the respondents from the Accounting Education Student 2015 State University of Yogyakarta amounted to 63 students. Data collection techniques using a questionnaire. The data analysis technique uses multiple regression analysis. The results showed: 1) There was no significant effect of Microteaching Quality on Readiness to Become Professional Teacher with   = -0.317 and significance value of 0.752. 2) There was a positive and significant effect of Guided Field Practice (PLT) on Readiness to Become Professional Teacher with = 3.963 and significance value of 0,000. The determination coefficient ( is 0.208 or 20.8%. These results identify that Readiness to Become Professional Teacher can be explained by the variable of Microteaching Quality and Guided Field Practice on 20.8%. Keywords: Microteaching, Guided Field Practice, Readiness to Become Professional Teacher